Penyajian Teknik Bernyanyi Pada Lagu No’Ufabu’U Karya Vian Waruwu: Indonesia - Noverman Lawolo; Manalu, Kartini R. M; Emmi Simangunsong (Visi Sosial Humaniora, 2026)
This study examines the presentation of singing techniques in the song No’ufabu’u composed by Vian Waruwu within the context of a recital performance. The purpose of this research is to analyze the application of vocal techniques and interpretative approaches used in performing the song. The study employs a qualitative approach with a descriptive method, utilizing observation, documentation, and reflective analysis of the author’s performative experience during the rehearsal process and the recital performance. The findings indicate that the performance of No’ufabu’u involves the application of various techniques, including both musical and vocal elements. The musical techniques encompass dynamics, tempo, legato, and staccato, while the vocal techniques include phrasing, breathing, and posture. These techniques are interconnected in supporting both the technical and expressive quality of the performance. Furthermore, the study identifies several challenges encountered during the performance process, particularly in breath control when singing high notes in measures 55–56, which require optimal respiratory management. The song No’ufabu’u is presented in a solo vocal format accompanied by a band ensemble consisting of electric guitar, bass guitar, drums, and piano. The success of the performance is not solely determined by the mastery of vocal techniques but also by physical readiness, the ability to maintain vocal quality, and the management of the performer’s health condition. This study is expected to contribute to the development of vocal technique studies, particularly in the presentation of regional songs within the context of musical performance.